Спектроскопическое исследование фотосенсибилизационных свойств галогензамещенных дипиррометеновых комплексов цинка - Носанов, Всеволод Сергеевич (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The work is devoted to an experimental study of the spectral-luminescent and photosensitization properties of halogen-substituted zinc dipyrromethene complexes. The quantum yields of singlet oxygen were determined by an indirect method using "trap" molecules of 1,3-diphenylisobenzofuran (DPBF). The possibility of efficient generation of singlet oxygen by molecules of metal complexes of dipyrromethenes is shown. The peculiarities of the influence of the nature of the introduced halogen substituent and the nature of the solvent on the obtained photosensitization characteristics are noted. The possibility of using the studied compounds as active media in the creation of new materials for photodynamic therapy and photocatalysis of oxidation reactions is discussed.